2008
DOI: 10.1074/jbc.m800426200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modification of Peroxiredoxin Is Associated with Drug-induced Apoptotic Signaling in Experimental Models of Parkinson Disease

Abstract: The aim of this study was to investigate changes in protein profiles during the early phase of dopaminergic neuronal death using two-dimensional gel electrophoresis in conjunction with mass spectrometry. Several protein spots were identified whose expression was significantly altered following treatment of MN9D dopaminergic neuronal cells with 6-hydroxydopamine (6-OHDA). In particular, we detected oxidative modification of thioredoxin-dependent peroxidases (peroxiredoxins; PRX) in treated MN9D cells. Oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 71 publications
4
82
0
Order By: Relevance
“…The role of Prx III in scavenging mitochondrial H 2 O 2 has been emphasized. Previous studies have shown that Prx III is vulnerable to inactivation through hyperoxidation of its active site cysteine residues in cells and rodent tissues under oxidative stress (25)(26)(27)(28)(29)(30)(31)(32)(33). Sulfinic Prx III can be specifically reduced back to the thiol form in mammalian cells (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Prx III in scavenging mitochondrial H 2 O 2 has been emphasized. Previous studies have shown that Prx III is vulnerable to inactivation through hyperoxidation of its active site cysteine residues in cells and rodent tissues under oxidative stress (25)(26)(27)(28)(29)(30)(31)(32)(33). Sulfinic Prx III can be specifically reduced back to the thiol form in mammalian cells (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…These three proteins make up a primary line of defense against H 2 O 2 in mitochondria. Like cytosolic Prx I and Prx II, mitochondrial Prx III is hyperoxidized and inactivated in cells under oxidative stress (25)(26)(27)(28)(29)(30)(31)(32)(33). Hyperoxi-dized Prx III is promptly regenerated to protect cells from mitochondrial H 2 O 2 -mediated oxidative damage (25)(26)(27).…”
mentioning
confidence: 99%
“…The parent vector was used as a control. Stable cell lines overexpressing Myc-tagged (MN9D/ m-Bak) or FLAG-tagged Bak (MN9D/f-Bak) were also established and characterized, as described previously (31). The stable cell lines were cultured in DMEM supplemented with 10% FBS and 500 g/ml G-418 (A.G. Scientific, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Such highly localized effects-redox signaling is well known to be a highly localized phenomenon-would support a very high gradient of peroxide concentrations around sites of ROS generation, but prevent the flood. Whether or when this floodgate effect would be operational is as yet unclear; while a number of reports link H 2 O 2 treatment of cells with Prx hyperoxidation (21,62,65,92), there are only a few publications that describe physiological stimuli that induce significant amounts of Prx hyperoxidation [e.g., during TNFa treatment of Leydig cells to induce apoptosis, and by 6-hydroxydopamine stimulation of dopaminergic neurons used as a model of Parkinson's disease (44,65)]. If the effect is indeed highly local, however, it may be that only very small amounts of Prx hyperoxidation are needed, amounts that are difficult to detect within the large pool of Prxs.…”
Section: Mechanisms For Thiol Peroxidase Redox Switches In Higher Orgmentioning
confidence: 99%